SIGNS AND SYMBOLS IN TRADITIONAL BUBAK KAWAH IN JOMBANG DISTRICT - Muhibatul Imamah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This study aims to determine the relationship between signs and symbols in the traditional Bubak craterusing the semiotic theory. This type of research is qualitative using the semiotic theory. There are 18 semioticaspects in this study. Data collection techniques used observation, interviews and translites. The data analysisprocedure was carried out by reading the data, selecting the data and entering the data into the initial analysistable. Based on the results of the research, it shows that the ritual order in the Bubak Kawah traditionalprocession in Gudo District, Jombang Regency, has 8 signs which are obtained in each sequence of the BubakKawah traditional procession. While the ubo rampe or equipment in the Bubak Kawah Traditional Procession inGudo District, Jombang Regency has 10 symbols, which symbols are obtained on the equipment set at the BubakKawah traditional procession. Furthermore, there will be the meaning of each sign and symbol obtained at theBubak Kawah traditional procession